PEREDARAN OPIUM DI MINANGKABAU ABAD KE-19 - Muhammad Nasir (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2020)
This article discusses the history of Minangkabau in the 19th century AD. One of the themes of 19th century Minangkabau history is the Islamic reform movement promoted by religious groups commonly called the Padri movement. One of the central issues of the Padri movement was eradicating the habit of drinking alcoholism that occurred in Minangkabau society. The habit of smoking the drug that comes from boiling opium certainly indicates the existence of the drug on a large scale. Therefore, this article will present a picture of the opium trade in Minangkabau in the 19th century from upstream (providers) to downstream (dealers). It is hoped that this article will be useful as an explanation for the habit of smoking made in the Minangkabau community at that time.